Ammonium acrylate biomanufacturing by an engineered Rhodococcus ruber with nitrilase overexpression and double-knockout of nitrile hydratase and amidase. (1st December 2016) - Sun, Jizhe; Yu, Huimin; Chen, Jie; Luo, Hui; Shen, Zhongyao
Abstract: Rhodococcus ruber TH was selected as a parent strain to engineer for biomanufacturing of ammonium acrylate; the characteristics of this strain included accelerated growth rate, high cell tolerance and natively overexpressed nitrile hydratase (NHase). Transcriptome analysis revealed that the transcription levels of the native NHase, amidase and nitrilase were extremely high, moderate and extremely low, respectively. Through NHase-amidase double-knockout and amidase single-knockout, the engineered strains R. ruber THdAdN and R. ruber THdA were obtained for overexpression of a heterologous nitrilase from R. rhodochrous tg1-A6 using a urea-induced Pa2 promoter. The nitrilase activity toward substrate acrylonitrile in the engineered THdAdN(Nit) reached 187.0 U/mL at 42 h, threefold of that R. rhodochrous tg1-A6 and 2.3-fold of that of THdA(Nit). The optimal catalysis temperature and pH of the nitrilases in different cells exhibited no significant difference. Using the cells as catalysts, biomanufacturing of ammonium acrylate was performed under room temperature. When catalyzed by the engineered THdAdN(Nit), the titer and productivity of ammonium acrylate dramatically increased to 741.0 g/L and 344.9 g/L/h, which are the highest results reported to date.